The Mangrove Periwinkle Littoraria angulifera (Mollusca: Littorinidae) in the Urabá Gulf (Colombian Caribbean): Finding Ways in an Urbanizing Coast? - Ramos, Jhostin; Boto, Marco; Blanco-Libreros, Juan Felipe; Riascos, José M. (Frontiers in Marine Science, 2021)
Periwinkles (Littorinidae: genus Littoraria) are one of the very few molluscan clades showing an adaptive radiation closely associated to the mangrove habitat. However, pervasive land use changes associated to urbanization is prompting mangrove loss or degradation, with unknown consequences for mangrove-associated fauna. In the southern Colombian Caribbean, mangrove ecosystems have been encroached by human settlements and different populations of Littoraria angulifera (Lamarck, 1822) now inhabit anthropogenic intertidal substrates in urban areas, but the demographic traits of populations thriving in these novel environments are unknown. We studied the relative abundance and size structure of L. angulifera in remnant mangrove patches, woody debris and anthropogenic substrates (boulder seawalls and built structures) in 13 locations throughout the Urabá Gulf, a human-transformed tropical estuarine system. The abundance of L. angulifera was up to two orders of magnitude higher in anthropogenic than in quasi-natural or natural substrates. Snails also displayed a significant preference for wave protected positions in boulder seawalls and built structures exposed to heavy wave action, which was not previously reported in mangrove forests. Moreover, snail populations in anthropogenic substrate were consistently dominated by individuals of small sizes in comparison with mangroves or driftwood. We argue that the anthropogenic disturbances caused by the expansion of Turbo city during nearly one century in a coast formerly dominated by mangrove forests are providing novel and expanding habitats, whose quality might be good enough as to support high-density populations of L. angulifera. However, we hypothesize that shifted thermal regimes in hard and novel wave-exposed urban seascapes might also be prompting behavioral adjustments and the selection of smaller size ranges than those observed in mangrove forests.